Integrated control of diseases and pest of cassava (Manihot esculenta Crantz) - Lozano, J.C.; Bellotti, Anthony C. (International Center for Tropical Agriculture, 1979)
The reasons an integrated pest and disease control in cassava is justified are analyzed. Some cultural practices are listed that would lessen the problems caused by negative production factors within an ecosystem and would give high stable yields. Recommendations are given to maintain and enrich the existent natural biological control. Aspects related to var. resistance are discussed in detail. (CIAT)